Resistência de Echium olantagineum L. aos herbicidas inibidores deenzima acetolactato sintase (ALS) - Peruzzo, Sabrina Tolotti (2016)
Echium plantagineum L. (EHIPL) is a new threat to the areas where wheat is sown due to the resistance to ALS inhibitor herbicides. Aiming to confirm the E. plantagineum resistance to metsulfurom methyl herbicide, evaluate the existence of multiple and cross resistance, characterize the development and know the competitive ability of this species, experiments were led in the greenhouse in 2015. The experiment conducted to confirm the resistance to metsulfurom methyl herbicide consisted of the use of biotype with suspected resistance (biotype R) and susceptible (biotype S) and ten increasing doses of the herbicide. The control, dry matter (DM) and size reduction were evaluated. Regression was employed, using non-linear models for the adjustment of the dose-response curve. The R biotype performed high degree of resistance to metsulfurom methyl herbicide. To evaluate the existence of multiple and cross resistance and control with alternative herbicides, the experiment consisted of the combination of R and S biotypes and 9 herbicides (metsulfurom methyl, saflufenacil, iodossulfurom imazethapyr methyl, cloransulam methyl, paraquat, bentazone, 2,4- D, glyphosate) and control without application. Control and DM were assessed. The biotype R has cross-resistance to ALS enzyme inhibiting herbicides. However does not have multiple resistance to glyphosate, bentazone, safufenacil, 2,4-D and paraquat demonstrating that such herbicides may be used as an alternative control. For growth analysis, the R and S biotypes and eight times assessments were used. Leaf area and DM were analyzed and from these assessments, the relative growth rate (RGR), absolute growth rate (AGR) and crop growth rate (CGR) was determined. Based on RGR is possible to infer that the R biotype shows higher growth and development than biotype S. To evaluate the competitive ability of the biotypes R and S in relation to the wheat crop, three experiments were conducted, arranged in series substitution: 1-wheat with biotype R, 2- wheat with biotype S and 3- biotype R with biotype S. The proportions were: 100:0, 75:25, 50:50, 25:75 and 0: 100. Competitiveness was analyzed through diagrams applied to replacement series and competitiveness indexes based on DM evaluation. The biotypes R and S have proved to be lesser competitive than wheat. The competitiveness of the R biotype was lesser than the S biotype.